EVALUATION OF ACCIDENTS AND COMPLICATIONS OF MAXILLARY THIRD MOLAR EXTRACTION - Mircea Riviș; Alexandra Roi; Ciprian Roi (Romanian Society of Oral Rehabilitation, 2023)
Aim and objectives: The present study aims is to observe and analyse the frequency of occurrence of accidents and complications of wisdom tooth extraction in a group of 60 patients, and the impact of the choice of different extraction techniques. Material and methods: This observational study analyses the statistical data obtain from 60 patients that presented for the extraction of the upper third molar. Demographic data, type of extraction techniques, occurrence of accidents during teeth extraction and the complications after the extractions were evaluated. Conclusions: Following this study, we can affirm that the intraoperative accidents occur in 33% of the cases and the complications of the wisdom teeth extractions appears in 15% of the patients.